Associations of concern: declining seagrasses and threatened dependent species. Issue 5 (10th October 2008) - Hughes, A Randall; Williams, Susan L; Duarte, Carlos M; Heck, Kenneth L; Waycott, Michelle
Abstract : Seagrasses are important marine foundation species that are reported to be declining worldwide, with almost 15% of species considered threatened. Seagrasses are highly productive plants that reconfigure water flow and influence nutrient cycling, as well as provide critical habitat for a wide array of fish and invertebrate species. Yet, many of these seagrass‐dependent species, including economically important fishes and invertebrates, are themselves in danger of overexploitation or extinction. In fact, there is on average more than one threatened associated species for every seagrass species across the globe. Links between threatened seagrasses and their dependent communities illustrate the importance of an ecosystem‐based management approach that incorporates interdependencies and facilitation among species.